Women, children and terrorism : social, economic and political costs (empirical investigation from Pakistan 2002-2015) - Zaman Bushra; Amin Amjad (Revista română de economie, 2017)
Today terrorism is confronted by the contemporary world in different forms and shapes. After the invasion of Afghanistan by the U.S and alliances of Pakistan with the U.S against Taliban, the socio-economic and political culture of Pakistan has completely changed. Pakistan is a participant in this Global War on Terror (GWO) for the last twelve years and trying to do more. This paper provides an exploratory analysis of victimization due to terrorism in Pakistan. The focus is on two questions; what are the latest challenges in form of victimization due to the evil of terrorism? And what key lessons and prevention can be to Pakistan in this terror situation? In today?s 21st century?s discourse of global terrorism, Pakistan spanning the border of Afghanistan is exposed to militancy and extremism. Today, about 50 Taliban groups are stationed and are hiding in seven different agencies of FATA in the name of Tehrik-e-Taliban (Al-Qaida), committing terrorism. By the year 2012-13, more than 52000 people including militants, civilians and law enforcing agencies have been killed. It has worst affects especially on the women and children of the area, who are the most vulnerable community. Consequently, direct cost is paid in the form of socio-economic and political instability. However not enough work has not been undertaken to highlight the socio economic and political implications of terrorism in Pakistan. This study has undertaken government effectiveness, political stability, foreign direct investment, primary level school enrolment of women and terrorism as the variables of primary concern along with graphs for a time period of 2001-02 to 2015. The findings emphasized that cost of war is mainly paid by women and children in public. Local government?s inability to provide security and political instability are the other major factors that contributed towards victimization in country.
2665773-9; 2344-4657; Revista română de economie; 717197875